The epidemiology of fasciolosis in the inter-Andean valley of Cajamarca, Peru. - Claxton, J.R. (1997)
Fasciolosis is recognised as a major problem in dairy cattle in parts of Peru. A longitudinal study of dairy cattle in Cajamarca, Peru was used to determine the annual pattern of infection with Fasciola hepatica. After a gradual increase from January, peak egg production occurred in August/September and then dropped rapidly. Indirect indicators of infection, eosinophil counts and serum liver-enzyme activities, indicated that the major period of new infection in cattle occurred from December to May each year. Examination of snails demonstrated that, although there was no clear annual cycle in snail abundance, the majority of snails infected with cercariae were found between January and March. Climatological data indicated that there was sufficient moisture for development of the parasite during a limited period each year, coinciding with the period of maximum abundance of cercaria-infected snails, but that irrigation could substantially alter the amount of water available. Infections in tracer-calves decreased from December to September, with little or no infection occurring between June and August, but suggesting that there could be significant infection prior to December. Thus a defined annual cycle of infection was observed, where cattle acquired infection from December to May and this infection matured to produce peak egg counts in August/September which were then available to infect the intermediate host for the next cycle of infection.